A compact-sized surface EMG sensor for myoelectric hand prosthesis - Prakash, A.; Sharma, S.; Sharma, N. (Springer Verlag, 2020)
Myoelectric prosthesis requires a sensor that can reliably capture surface electromyography (sEMG) signal from amputees for its controlled operation. The main problems with the presently available EMG devices are their extremely high cost, large response time, noise susceptibility, less amplitude sensitivity, and larger size. This paper proposes a compact and affordable EMG sensor for the prosthetic application. The sensor consists of an electrode interface, signal conditioning unit, and power supply unit all encased in a single package. The performance of dry electrodes employed in the skin interface was compared with the conventional Ag/AgCl electrodes, and the results were found satisfactory. The envelope detection technique in the sensor based on the tuned RC parameters enables the generation of smooth, faster, and repeatable EMG envelope irrespective of signal strength and subject variability. The output performance of the developed sensor was compared with commercial EMG sensor regarding signal-to-noise ratio, sensitivity, and response time. To perform this, EMG data with both devices were recorded for 10 subjects (3 amputees and 7 healthy subjects). The results showed 1.4 times greater SNR values and 45% higher sensitivity of the developed sensor than the commercial EMG sensor. Also, the proposed sensor was 57% faster than the commercial sensor in producing the output response. The sEMG sensor was further tested on amputees to control the operation of a self-designed 3D printed prosthetic hand. With proportional control scheme, the myoelectric hand setup was able to provide quicker and delicate grasping of objects as per the strength of the EMG signal. © 2019, Korean Society of Medical and Biological Engineering.
Keywords: Surface electromyography; Myoelectric prosthesis; Signal-to-noise ratio (SNR); Control scheme; Grasp types